The Role of Traffic Education (Dikmas Lantas) Through Social Media in an Effort to Prevent Traffic Violation - Ananda, Mesya (Police Studies Review, 2024)
The district of Cirebon is one of the regions that encounter enhancement of traffic violation in Indonesia. The key to overcome traffic violation is to do preemptive effort which is to give traffic education (Dikmas Lantas) to upgrade the society’s awareness to maintain traffic order and safety. Dikmas Lantas via social media resolve problems that have existed in common Dikmas Lantas programs that’s related to limited target, budget, time, and place. The purpose of this research is to describe the mechanism, to analyze the role, and to identify factors that affect Dikmas Lantas via social media in an attempt to prevent traffic violation by Satlantas Polresta Cirebon. The theories that are used in this research is The Theory of Communication, The Theory of Management, and The Theory of Role. While the concepts that are used in this research is The Concept of Traffic Violation, The Concept of Dikmas Lantas, and The Concept of Social Media. Method of research that is used is qualitative approach with field research as the type of research. Data was obtained from interview results, observation also document studies and are analyzed by data reduction, data presentation, and drawing conclusions. Data triangulation is used as data validity technique. The location of the research is in Polresta Cirebon. The conclusion of the research is the role of Dikmas Lantas via social media have been done properly but there are still obstacles and deficiency in the process of planning, organizing, and actuating the program. Factors that affect the program consist of money, method, and machine as support factor whilst man, aterials, and market as inhibitor factor. The suggestion that’s given is to complete the administration, to conduct development education and training for personnel, to expand the platform of Dikmas Lantas via social media, and to check the society’s comprehension, also to increase socialization of the program.